PENGARUH DISPLIN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT ASTRA LIFE TANGERANG SELATAN - Dimas Arya Putra (Al Hasanah Barokah Foundation, 2024)
The aim of this research is to find out whether there is an influence of Work Discipline and Leadership Style, either individually or simultaneously, on employee performance at PT Astra Life, South Tangerang. This research uses an associative quantitative research method, data obtained in the form of a questionnaire. The result is that there is an influence of work discipline on employee performance as evidenced by the t calculated value of the work discipline variable being 5,742 which is greater than the t table of 1.99085 with a significance level of 0 which is greater than 0.05, so it can be interpreted that Ha is accepted and Ho is rejected. Leadership Style on Employee Performance is proven by the tcount value of the Leadership Style variable being 3.072 which is greater than the ttable of 2.00172 with a significance level of 0.03 which is greater than 0.05 so it can be interpreted that Ha is accepted and Ho is rejected. Work Discipline and Leadership Style on Employee Performance Ftable value at a significance level of 0.05 with df 1 (number of variables -1) 3-1 = 2, and df 2 (n-k-1) or = 60-2-1 = 57 obtained value F table is 3.16 So it can be concluded that Fcount > Ftable (33.926 > 3.16) and significance < 0.05 (0 < 0.05), then Ha is accepted, so it can be concluded that Work Discipline and Leadership Style together influence Employee Performance